Multi-mode Motion Opening Mechanism Design for Aircraft Door Based on the Bricard Mechanism - Peng Renhui; Hang Lubin; Wu Borui; Wu Yang; Qiu Xudong (Jixie chuandong)
The aircraft door must be smoothly linked with the outer surface of the fuselage and realize the sealing function of the inner and outer boundaries of the fuselage at the same time. The normal opening and closing can be realized only when the position and posture of the door relative to the fuselage are corrected. In view of the fact that the opening branch chain of the existing lifting arm 4R mechanism linked in series with the large hinge arm mechanism cannot adjust the position and attitude of the aircraft door in all directions, a new aircraft door opening branch chain is proposed, which uses the plane-symmetric Bricard mechanism instead of the 4R mechanism, and forms a three branch chain aircraft door opening parallel mechanism with the parallel rod mechanism 2-S-S branch chain. Based on the orientation feature set theory of parallel mechanism, the azimuth feature set analysis of door opening mechanism under different modes is carried out. It is verified that the 6R mode, 4R mode and mode switching of serial large hinge arm surface symmetrical Bricard mechanism can realize the lifting of aircraft door and the adjustment of omnidirectional position and attitude. The orientation feature set of the mechanism reveals that the lifting, adjustment and rotation motion of the opening mechanism has a degree of freedom, and three motion modes with different independent elements are selected：6R lifting, spherical 4R adjustment movement and large hinge arm rotation during door opening. When the Bricard mechanism is embedded, the aircraft door can be coupled and adjusted in three directions, which provides a new idea for the design of aircraft door.